Light concentric exercise has a temporarily analgesic effect on delayed-onset muscle soreness, but no effect on recovery from eccentric exercise - Zainuddin, Zainal; Sacco, Paul; Newton, Mike; Nosaka, Kazunori (National Research Council Canada, 2006)
This study investigated the hypothesis that a bout of light concentric exercise (LCE) would alleviate delayed-onset muscle soreness (DOMS) and enhance recovery from muscle damage. Fourteen subjects performed two bouts of 60 maximal eccentric actions of the elbow flexors (Max-ECC) separated by 2-4 weeks. One arm performed LCE (600 elbow flexion and extension actions with minimal force generation) 1, 2, 3, and 4 d after Max-ECC; the contralateral (control) arm performed only Max-ECC. Changes in maximal isometric and isokinetic strength, range of motion (ROM), upper arm circumference, and muscle soreness and tenderness were assessed before and immediately after LCE bouts. Changes in these measures and plasma creatine kinase (CK) activity for 7 d after Max-ECC were compared between the control and LCE arms using 2-way repeated measures analysis of variance (ANOVA). Significant (p < 0.05) decreases in muscle soreness (∼40%) and tenderness (∼40%) were evident immediately after LCE, which also resulted in small but significant decreases in strength (∼15%) and increases in ROM (∼5°). No significant differences in the changes in the measures following Max-ECC were observed between the arms. These results suggest that LCE has a temporary analgesic effect on DOMS, but no effect on recovery from muscle damage.